The Influence of Islamic Financial Literacy and Peer Influence on Islamic Entrepreneurial Behavior of UIN North Sumatra Medan Students - Fadilah, Tasya; Imsar; Jannah, Nurul (MALIA: Jurnal Ekonomi Islam, 2026)
Introduction: Islamic entrepreneurial behavior views business activities not merely as a means of profit, but as an implementation of the values ​​of monotheism, trustworthiness, justice, and welfare. However, student entrepreneurial interest remains relatively low, while Islamic financial literacy and social environmental influences are suspected to be important factors in shaping Islamic value-based business behavior. This study aims to analyze the influence of Islamic financial literacy and peer influence on Islamic entrepreneurial behavior among students at UIN Sumatera Utara Medan. Methods: The study used a quantitative approach with a survey method on 100 students selected through simple random sampling. Data were collected using a Likert scale questionnaire and analyzed using multiple linear regression using SPSS 22. Instrument tests, classical assumptions, t-tests, F-tests, and coefficients of determination were used to test the hypotheses. Results: The results show that Islamic financial literacy has a positive and significant effect on Islamic entrepreneurial behavior (t = 10.637; p < 0.05). Conversely, peer influence has no significant partial effect (t = 0.134; p > 0.05). Simultaneously, both variables have a significant effect (F = 57.252; p < 0.05) with an explanatory contribution of 54.1%. Conclusion and suggestion: Sharia financial literacy is a primary factor in shaping Islamic entrepreneurial behavior, while peer influence is supportive. Strengthening the entrepreneurship curriculum based on the principles of sharia, training in Islamic financial literacy, and developing students' spiritual character are recommended to foster ethical, independent, and blessing-oriented entrepreneurs.